Answer:
(3)
Step-by-step explanation:
(1), (2) and (4)
can be written as Fr= p1-p2, F and r are inversely proportional
(3) r is directly proportional with F which is opposite to the given formula
hence this is incorrect
First answer: 160
Second answer: 300
Answer:
{1, (-1±√17)/2}
Step-by-step explanation:
There are formulas for the real and/or complex roots of a cubic, but they are so complicated that they are rarely used. Instead, various other strategies are employed. My favorite is the simplest--let a graphing calculator show you the zeros.
___
Descartes observed that the sign changes in the coefficients can tell you the number of real roots. This expression has two sign changes (+-+), so has 0 or 2 positive real roots. If the odd-degree terms have their signs changed, there is only one sign change (-++), so one negative real root.
It can also be informative to add the coefficients in both cases--as is, and with the odd-degree term signs changed. Here, the sum is zero in the first case, so we know immediately that x=1 is a zero of the expression. That is sufficient to help us reduce the problem to finding the zeros of the remaining quadratic factor.
__
Using synthetic division (or polynomial long division) to factor out x-1 (after removing the common factor of 4), we find the remaining quadratic factor to be x²+x-4.
The zeros of this quadratic factor can be found using the quadratic formula:
a=1, b=1, c=-4
x = (-b±√(b²-4ac))/(2a) = (-1±√1+16)/2
x = (-1 ±√17)2
The zeros are 1 and (-1±√17)/2.
_____
The graph shows the zeros of the expression. It also shows the quadratic after dividing out the factor (x-1). The vertex of that quadratic can be used to find the remaining solutions exactly: -0.5 ± √4.25.
__
The given expression factors as ...
4(x -1)(x² +x -4)
To obtain x, we can sum the angles < AQB and < BQC
=> 5X + 8X - 24
=> 13X -24
we are also told that that the sum of their angles is 80
13X - 24 = 80
13 X = 24 + 80
13X = 104
Divide both sides by 13
x = 104/13
x = 8
Answer:
B
Step-by-step explanation:
since 5 is constant so you can take it out from the summation